Specific versus Nonspecific Isothermal DNA Amplification through Thermophilic Polymerase and Nicking Enzyme Activities() - Tan, Eric (2008)
Rapid isothermal nucleic acid amplification technologies can enable diagnosis of human pathogens and genetic variations in a simple, inexpensive, user-friendly format. The isothermal exponential amplification reaction (EXPAR) efficiently amplifies short oligonucleotides called triggers in less than 10 min by means of thermostable polymerase and nicking endonuclease activities. We recently demonstrated that this reaction can be coupled with upstream generation of trigger oligonucleotides from a genomic target sequence, and with downstream visual detection using DNA-functionalized gold nanospheres. The utility of EXPAR in clinical diagnostics is, however, limited by a nonspecific background amplification phenomenon, which is further investigated in this report. We found that nonspecific background amplification includes an early phase and a late phase. Observations related to late phase background amplification are in general agreement with literature reports of ab initio DNA synthesis. Early phase background amplification, which limits the sensitivity of EXPAR, differs however from previous reports of nonspecific DNA synthesis. It is observable in the presence of single-stranded oligonucleotides following the EXPAR template design rules and generates the trigger sequence expected for the EXPAR template present in the reaction. It appears to require interaction between the DNA polymerase and the single-stranded EXPAR template. Early phase background amplification can be suppressed or eliminated by physically separating the template and polymerase until the final reaction temperature has been reached, thereby enabling detection of attomolar starting trigger concentrations.